2002
DOI: 10.1136/emj.19.6.584
|View full text |Cite
|
Sign up to set email alerts
|

Importance of emergency identification schemes

Abstract: Background: Millions of people worldwide may have a hidden medical condition that could endanger their life in an emergency. These conditions may include cardiac conditions, severe allergies, or diabetes. Emergency identification schemes such as Medic Alert produce emblems that alert health care professionals to potential problems and can ensure appropriate and prompt treatment. This paper uses mechanical failure of the Björk-Shiley convexo-concave (BSCC) heart valve as an example of a hidden medical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…Since the early 90s, criminologists have begun to question the nature of everyday forensic science practices [1][2][3][4][5][6][7][8][9][10], with obvious consequences for its related ethics and deontology [11][12][13][14]. It appears that the 1993 US Daubert hearing not only challenged the nature of the various fields of forensic science [15][16][17], but also our understanding of the nature of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 90s, criminologists have begun to question the nature of everyday forensic science practices [1][2][3][4][5][6][7][8][9][10], with obvious consequences for its related ethics and deontology [11][12][13][14]. It appears that the 1993 US Daubert hearing not only challenged the nature of the various fields of forensic science [15][16][17], but also our understanding of the nature of evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Accident and Emergency (A & E) departments have a central role to play in tackling the problem of medicines’ overdose as most patients present there prior to admission to hospital or other specialized unit (1, 2).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that an EMI medallion worn on the body is better at identifying patients than an EMI card placed in a wallet [2,6,8]. Morton et al [6] found that although 99% of medical personnel had heard of body-worn medical emblems, only 5-10% were aware that patients could be carrying important medical information in another form [6].…”
Section: Introductionmentioning
confidence: 99%